Impact of Three Safety Interventions Targeting Off-Label Use of Immediate-Release Fentanyl on Prescription Trends: Interrupted Time Series Analysis - García-Sempere, Aníbal; Hurtado, Isabel; Peiró, Salvador; Sánchez-Sáez, Francisco; Rodríguez-Bernal, Clara Liliana; Puig-Ferrer, Magda; Escolano, Manuel; Sanfélix-Gimeno, Gabriel (Frontiers in Pharmacology, 2022)
Background: The Spanish health authorities are concerned by the off-label use of immediate-release formulations of fentanyl (IRF) in noncancer pain and cancer pain in patients with no chronic pain therapy. Aim: To evaluate the impact of different interventions to improve appropriateness of IRF prescription on off-label prescription. Patients and methods: We used interrupted time series (ITS) to estimate immediate and trend changes of IRF prescription for noncancer pain (NCP) and breakthrough cancer pain (BCP) in patients with and without chronic cancer pain therapy associated with two medication reviews (I1 and I2) and the issue of a safety warning letter (I3) with data from a Spanish region with 5 million inhabitants, from 2015 to 2018. Results: The use of IRF for NCP in the region Valencia was reduced from about 1,800 prescriptions per week to around 1,400. The first medication review was followed by an immediate level change of −192.66 prescriptions per week (p < 0.001) and a downward trend change of −6.75 prescriptions/week (p < 0.001), resulting in a post-intervention trend of −1.99 (p < 0.001). I2 was associated with a trend change of -23.07 (p < 0.001) prescriptions/week. After I3, the trend changed markedly to 27.23 additional prescriptions/week, for a final post-intervention trend of 2.17 (p < 0.001). Controlled-ITS provided comparable results. For potentially inappropriate BCP use, the second medication review was followed by a downward, immediate level change of −10.10 prescriptions/week (p = 0.011) and a trend change of 2.31 additional prescriptions/week (p < 0.001) and the issue of the safety warning (I3) was followed by a downward trend change of −2.09 prescriptions/week (p = 0.007). Conclusion: Despite IRF prescription for NCP decreased, the interventions showed modest and temporary effect on off-label prescription. Our results call for a review of the design and implementation of safety interventions addressing inappropriate opioid use.